2021
DOI: 10.3389/fchem.2021.769620
|View full text |Cite
|
Sign up to set email alerts
|

Multielement Characterization and Antioxidant Activity of Italian Extra-Virgin Olive Oils

Abstract: Food product safety and quality are closely related to the elemental composition of food. This study combined multielement analysis and chemometric tools to characterize 237 extra-virgin olive oil (EVOO) samples from 15 regions of Italy, and to verify the possibility of discriminating them according to different quality factors, such as varietal or geographical origin or whether they were organically or traditionally produced. Some elements have antioxidant properties, while others are toxic to humans or can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Despite the limited data on REE contents available in the literature, the concentration range that we detected ranged between 0.09 and 4.22 ng g −1 , in accordance with the results of different authors, which were well summarized in a recent study [ 69 ], who reported ranges varying between 0.002 and 7 ng g −1 in olive oils from costal region. Our values also agree with those described by other authors in other areas [ 2 , 70 , 71 , 72 ]. In descending order, the most abundant REEs were Ce, Y, La, and Nd, which had mean values of 3.27, 2.18, 1.53, and 1.36 ng g −1 , respectively.…”
Section: Resultssupporting
confidence: 93%
“…Despite the limited data on REE contents available in the literature, the concentration range that we detected ranged between 0.09 and 4.22 ng g −1 , in accordance with the results of different authors, which were well summarized in a recent study [ 69 ], who reported ranges varying between 0.002 and 7 ng g −1 in olive oils from costal region. Our values also agree with those described by other authors in other areas [ 2 , 70 , 71 , 72 ]. In descending order, the most abundant REEs were Ce, Y, La, and Nd, which had mean values of 3.27, 2.18, 1.53, and 1.36 ng g −1 , respectively.…”
Section: Resultssupporting
confidence: 93%
“…Consequently, the assurance of authenticity, high quality and purity of olive oil is a matter of great importance. For this purpose, investigating olive oil by means of ICP-MS analysis gains widespread scientific attention [ 9 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A considerable amount of literature has been published on Spanish, Italian, Tunisian, and Greek olive oil varieties.…”
Section: Discussionmentioning
confidence: 99%
“…10 The advantages of lipidomics in the analysis of degraded vegetable oils and animal fats are: (1) lipidomics is not the analysis of individual lipids, but the simultaneous study of whole lipids, analyzing vegetable oils and animal fats from a systematic perspective; [11][12][13] (2) lipidomics has led us to identify new signaling molecules, discover potential biomarkers for differences in vegetable oils and animal fats, and provide effective assistance for the distinction and traceability of vegetable oils and animal fats. [14][15][16] The innovation points of this study include: (1) compared with previous studies, this paper analyzes more types and quantities of samples and dynamically monitors the changes in the lipid composition and content of 13 different types of vegetable oils and animal fats during aging on ve different carriers; (2) solves the problem of difficult identication of aged vegetable oils and animal fats in forensic science. This paper simulates the changes in the lipid composition and content of vegetable oils and animal fats during aging on ve different carriers under extremely hot conditions.…”
Section: Introductionmentioning
confidence: 99%
“…10 The advantages of lipidomics in the analysis of degraded vegetable oils and animal fats are: (1) lipidomics is not the analysis of individual lipids, but the simultaneous study of whole lipids, analyzing vegetable oils and animal fats from a systematic perspective; 11–13 (2) lipidomics has led us to identify new signaling molecules, discover potential biomarkers for differences in vegetable oils and animal fats, and provide effective assistance for the distinction and traceability of vegetable oils and animal fats. 14–16…”
Section: Introductionmentioning
confidence: 99%